Lasers in gynecology: possibilities and limitations ; with 105 tables - Bastert, Gunther; Wallwiener, Diethelm; Pollmann, Dirk (Springer, 1992)
A synopsis of the use of lasers in gynecology is presented in this book; it is supported by more than 10 years of experience and backed up by studies inthe fields of experimental surgery, technical medicine and clinical gynecology. The authors show how laser-assisted preparation hasbroadened the spectrum of operative possibilities in gynecology. Major points of attention are experimental surgery and basic research, details of application with respect to specific indications, and future potential. Furthermore, the clear definition of the possibilities and limitations of laser technology puts an end to the highly stylized view of a patent wonder divorced from general operative standards. Thereis no doubt that users of laser technology stand on the threshold of a promising development and yet, despite the present elegant applications, thefirst steps to maturity are only now being taken
Keywords: Laser; Gynäkologie; Laserchirurgie; Frauenkrankheit